Neural regulation of mesenchymal stem cells in craniofacial bone: development, homeostasis and repair - Pi, Huai-Jin; Huang, Bo; Yuan, Quan; Jing, Jun-Jun (Frontiers in Physiology, 2024)
Mesenchymal stem cells endow various functions, including proliferation, multipotency, migration, etc. Craniofacial bones originate from the cranial neural crest and are developed mainly through intramembranous ossification, which are different from long bones. There are varied mesenchymal stem cells existing in the craniofacial bone, including Gli1 + cells, Axin2 + cells, Prx1 + cells, etc. Nerves distributed in craniofacial area are also derived from the neural crest, and the trigeminal nerve is the major sensory nerve in craniofacial area. The nerves and the skeleton are tightly linked spatially, and the skeleton is broadly innervated by sensory and sympathetic nerves, which also participate in bone development, homeostasis and healing process. In this review, we summarize mesenchymal stem cells located in craniofacial bone or, to be more specific, in jaws, temporomandibular joint and cranial sutures. Then we discuss the research advance concerning neural regulation of mesenchymal stem cells in craniofacial bone, mainly focused on development, homeostasis and repair. Discovery of neural regulation of mesenchymal stem cells may assist in treatment in the craniofacial bone diseases or injuries.